THE RELATION OF MARKETING MIX WITH CUSTOMERS LOYALTY IN LABORATORY CLINICAL OF PRODIA PALU - Oktavia, Sriyani; Sudirman, Sudirman; Kadri, Abdul (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2016)
ABSTRACT Clinical Laboratory of Prodia has fluctuated significant number of patient visits from 2014 through 2015, a decrease in the number of older patients indicating a decreased patient loyalty. Therefore Prodia need to design marketing programs by applying the marketing mix. Includes aspects of the marketing mix of product, price, place, promotion, people, process and physical evidence. This study aims to determine the relationship of the marketing mix with Customer Loyalty in the Clinical Laboratory Prodia Palu. This research is an analytical survey with cross sectional design. Location of the study in the Clinical Laboratory of Prodia Palu. The research was conducted in March-April. Total sample of 98 respondents, taking by consecutive sampling. The bivariate analysis of loyalty using chi square test showed that: Product no correlation (P = 0.028 <0.05), Price no correlation (P = 0.139 > 0.05), place no correlation (P = 1.00> 0.05), promotion there is a correlation (P = 0.004 <0.05), people no correlation (P = 0.236> 0.05), there is a correlation process (P = 0.040 <0.05) and physical evidence there is a correlation (P = 0.007 < 0.05). From the results of the chi square test price, place and people has not correlation with customer loyalty, so it is suggested that the management of Prodia can improve marketing strategy that oriented to price, place and people to increase customer loyalty. Keywords : Marketing Mix, price, place, people, customer loyalty